Android-Based Mobile Learning Application Design: Its Implementation and Evaluation for Aiding Secondary School Students' to Study Inorganic Compound Nomenclature - Kurniawan, C.; Dhiyaulkhaq, M.; Wijayati, N.; Kasmui, K.; Nasekhah, D.; Ismail, M. H. (Jurnal Pendidikan IPA Indonesia, 2022)
Inorganic compound nomenclature is one of the most basic concepts in chemistry. Therefore, for students, correct naming of the chemicals is essential before learning advanced chemistry. However, nomenclature as a learning topic consists of rules and thus requires frequent practice. Tenth graders will face difficulties if they have remember thousands of the chemicals' names. The objective of this research is to develop and validate the effectiveness of android-based learning media to help students in learning chemical compound nomenclature. In order to meet the goal, this study was conducted in stages; they are (1) information collection, (2) planning, (3) product draft development, (4) small-scale trials, (5) product revisions, and (6) large-scale trials. The effectiveness of the examined mobile-app was measured using post-test questions, resulting in 87.88% student completion. Furthermore, since experts have been in agreement concerning the validity of the examined mobile app – both the content and the media, the app can be used for learning process.